Search for oil deposits in YuS2–3 formations of the Southern part of the Priobskoye field based on a seismogeological model using exchromaSG technology - D. A. Kotunov; S. A. Khalilov; D. V. Romanov; S. A. Lyubimov (Известия высших учебных заведений: Геология и разведка)
Background. Development of an oil field at the third stage causes certain difficulties for a subsoil user associated with the falling oil production, which requires additional measures to replenish the resource base. In addition to clarification of the geological structure of the deposit under development, the search for new oil deposits contributes to increasing the available reserves thus reducing the rate of decline in production. The availability of geological models for promising objects, created based on modern approaches to processing and interpretation of 3D seismic data, increases the efficiency of geological exploration and reduces the production costs. In the Southern license area of the Priobskoye field, its Jurassic interval is considered to be a promising area for exploration, given that the confirmed productivity of the Tyumen Formation in a large number of fields in the Khanty-Mansi Autonomous Okrug–Yugra.   Aim. To develop a conceptual geological model of the YuS2–3 formations, which is the most promising part of the Middle Jurassic strata in terms of oil potential, by re-processing and re-interpretation of seismic data for the entire license area performed in 2020. A detailed analysis of information on the lithological structure and oil potential of the studied area.   Materials and methods. Mapping of potential hydrocarbon traps was performed taking the following factors into account: presence of oil mother strata, migration pathways, reservoir, cover and deposit integrity. Improving the reliability of these factors seems to be key to successful exploration. In our opinion, the assessment of two factors, i.e., migration pathways and reservoir presence, can be significantly improved with the help of paleogeographic interpretations based on chromatic processing of eXchromaSG seismic.   Results. The results of conceptual modeling were used in planning of exploration works. The results were validated during implementation of the exploration drilling program in 2021—2022. The drilling results confirmed the oil bearing capacity of the upper part of the Tyumen Formation.   Conclusion. The application of the hydrocarbon prospecting methodology based on seismofacial analysis of Jurassic sediments confirmed the oil-bearing potential of the Southern license area of the Priobskoye field, thereby increasing the resource base by discovering new deposits.